Apologetics and theology through beauty - Medina Balguerías, Marta (Razón y fe, 2022)
Returning to the intuition of Henri de Lubac in his lecture “Apologetics and theology”, this article suggests proposing and defending faith today through a theological and spiritual deepening in which faith, life, rationality, and mysticism go hand in hand. Beauty is also presented as the most fruitful spiritual key to talk about God today, departing from the diversity that exists in the way of understanding and approaching it and offering a hermeneutic criterion (love) to establish a hierarchy among the different forms of beauty. Finally, to use the path of beauty as a path of conversion is proposed as a prophetical offer to today’s society.